PENGARUH TEMAN SEBAYA TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMP NEGERI 19 PONTIANAK - Marta Nensi; Aminuyati Aminuyati; F.Y. Khosmas (Universitas Tanjungpura, 2020)
Abstract This research aimed to find out the influence of friends of the same age (peers) on the students’ learning outcomes at class VII C Science (IPS) OF SMPN 19 Pontianak. The research method used was descriptive in the form of quantitative research. The research sample was 30 students of class VII C. The data collected was in the form of a questionnaire comprising five indicators, namely learning to solve problems with friends, gaining emotional encouragement, friends as a substitute for family, being a study partner, and finding self-esteem. Based on the results of the data analysis, the friends of the same age frequency were 64.51% (20 students) with a high category. The learning outcomes of IPS subjects obtained a percentage of completion of 32.25% (10 students), categorized as moderate. The influence of peers on the learning outcomes was 0.462, with a significance of 0.05. Thus, the result of the t count ˃ t table, which is 4,990 ˃ 0.349. Henceforward, there is a positive influence between friends of the same age on the student learning outcomes in grade VII C SMPN 19 Pontianak. Keywords:Learning Outcomes, Peers, Social Sciences.